Menciptakan Keharmonisan Antar Etnis Melalui Pemanfaatan Instagram Untuk Edukasi Kampanye PILPRES 2024: Menciptakan Keharmonisan Antar Etnis Melalui Pemanfaatan Instagram Untuk Edukasi Kampanye PILPRES 2024 - Iwan Setiadi; Setiadi, Iwan (LPPM UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
Abstract Inter-ethnic harmony is very important to maintain the harmony and integrity of society. The research aims to describe the influence of Instagram educational content on students' awareness of the importance of inter-ethnic harmony in facing the 2024 presidential election. The research uses quantitative descriptive methods. The research population was students of MAS Al Wathoniyah 43 Jakarta with a total research sample of 30 students taken by purposive sampling. The research instruments used questionnaires and interviews as well as document analysis. Instagram educational content is created by researchers. The research results show that the influence of Instagram educational content on awareness of the importance of inter-ethnic harmony in facing the 2024 presidential election for students is in the very high category. Another finding from this research is that students who have the right to vote in the 2024 presidential election gain knowledge about the profile of presidential candidates that they did not previously know. Thus, this research concludes that educational content distributed via the Instagram platform has a very strong influence in increasing students' understanding of the importance of maintaining inter-ethnic harmony in facing the 2024 presidential election. Key words: Inter-ethnic harmony, Instagram, 2024 presidential election, education of student